Factors Affecting Carbon Emission Trading Price: Evidence from China. Issue 15 (8th December 2019) - Yin, Yingkai; Jiang, Zhihui; Liu, Yazhou; Yu, Zheng
ABSTRACT: Since the Chinese national carbon trading market was launched in 2017, the carbon trading price has become an important research topic. This study constructs the 'China carbon trading price index', and then a SVAR model with the China carbon trading price index, the EU carbon trading price index, an industrial index, the China Securities Index energy index (CSI), an air quality index (AQI) and the HS300 to study carbon trading prices in China. The result shows that the EU carbon trading price and AQI have a direct effect on China carbon trading price. Meanwhile, the CSI energy index, industrial index and HS300 have an indirect effect on the carbon trading price, and the effect is slightly positive. In addition, the volatility of China's carbon trading price is mainly internally driven, while the volatility of the other economic variables examined is mostly driven by the EU carbon trading price index and the industrial index.